2016
DOI: 10.1097/qad.0000000000001127
|View full text |Cite
|
Sign up to set email alerts
|

Targeting elimination of mother-to-child HIV transmission efforts using geospatial analysis of mother-to-child HIV transmission in Zimbabwe

Abstract: Background We assessed Zimbabwe’s progress towards elimination of mother-to-child HIV transmission (eMTCT) under Option A. Methods We analyzed 2012 and 2014 cross-sectional serosurvey data from mother-infant pairs residing in the same 157 health facility catchment areas (CA) randomly sampled from 5 provinces. Eligible women were ≥16 years and mothers/caregivers of infants born 9–18 months prior. We aggregated individual-level questionnaire and HIV serostatus within CA or district to estimate MTCT and the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 8 publications
(17 reference statements)
1
20
0
Order By: Relevance
“…Over 90% coverage of recommended antiretroviral treatment/prophylaxis during pregnancy is also consistent with UNAIDS targets for global elimination of MTCT, however the drop to 85.6% at 6–10 weeks is a concern as it is below the UNAIDS target for ART during breastfeeding of 90%. [ 10 ] The coverage figures for mothers and babies combined compare favorably to other studies, such as 65% in Zimbabwe, [ 13 ] 26% in rural Kenya, [ 11 ]. These figures also suggest approximately 10% missed opportunities for antiretroviral therapy/prophylaxis per Rwandan protocol in mother-baby pairs.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Over 90% coverage of recommended antiretroviral treatment/prophylaxis during pregnancy is also consistent with UNAIDS targets for global elimination of MTCT, however the drop to 85.6% at 6–10 weeks is a concern as it is below the UNAIDS target for ART during breastfeeding of 90%. [ 10 ] The coverage figures for mothers and babies combined compare favorably to other studies, such as 65% in Zimbabwe, [ 13 ] 26% in rural Kenya, [ 11 ]. These figures also suggest approximately 10% missed opportunities for antiretroviral therapy/prophylaxis per Rwandan protocol in mother-baby pairs.…”
Section: Discussionsupporting
confidence: 55%
“…[ 9 ] Compared to regional studies of Option B or B+, this rate compares favorably to 10% MTCT found in Kenya and 6.7% in Zimbabwe. [ 12 , 13 ] The Rwanda national target is 2% at 18 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Southern and Eastern African countries such as Comoros, Malawi, Rwanda, South Africa, Burundi, and Uganda have seen a remarkable decline in MTCT transmission of HIV, many countries in West and Central Africa like Angola, Equatorial Guinea, the Gambia, Mali, and Niger have experienced an increase in transmission rate [2]. The intensification of the existing PMTCT program and scaling up of a nationwide program to accelerate MTCT elimination in Malawi, Zimbabwe, and South Africa have resulted in MTCT at 6-12weeks postpartum rate comparable to the 'global north' [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The current prevalence of HIV is estimated to be 14.6% among 15–64 year olds in Zimbabwe [ 24 ]. Despite notable reductions in the mother-to-child transmission rates, to 6.7%, at the population level [ 25 ], UNAIDS estimated that mother-to-child transmission is 6.39% [ 26 ]. The number of children orphaned due to AIDS is estimated as 524,581 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%